Chile Financial Sector Assessment Program : Detailed Assessment Report of CCLV (CCP), Contraparte Central, S.A. - World Bank Group (World Bank, Washington, DC, 2016)
Chile has fairly developed payment, clearing, and settlement infrastructures. Sistema liquidación bruta en tiempo real (real time gross settlement (LBTR) is largely compliant with the principles for financial market infrastructures (PFMI), and is sound from an operations perspective. ComBanc has been also assessed as sound from a (financial, operational) risk management perspective. Additional steps to improve compliance of ComBanc with the PFMI are warranted, especially with regard to governance arrangements and management of investments risk. Total of five FMIs were assessed as part of review of standards and codes (ROSC), although one of these operates both as a central counterparty (CCP) and as a securities settlement system (SSS) for different segments of the exchange-traded securities market, and as a result a total of six FMI assessments were produced by the team. In addition, the responsibilities of authorities for FMIs were assessed. The main tool used by the assessment was the CPSS-IOSCO assessment methodology for the principles for financial market infrastructure and the responsibilities of authorities. In addition to the self-assessments, other sources of information included the applicable laws and regulations, as well as each FMI’s main policies and internal documents (for example, detailed policies, and processes and procedures for certain key areas) which were shared by the FMIs with the assessors, and other information available at each FMI’s website (for example, statistics). The World Bank Group (WBG) and local teams also met with a number of users of these FMIs, including two large commercial banks and two brokers-dealers that are not part of local bank-lead conglomerates.